"That Man Patton": The Personal History of a Book. Issue 2 (3rd July 2019) - Brown, Duncan
Abstract : Alan Paton's novel, Cry, the Beloved Country: A Story of Comfort in Desolation (1984 [1948]), appeared around 70 years ago, and has been the subject of widely discrepant responses ever since its initial publication. It has sold millions of copies across the globe, appeared in multiple forms – abridged versions, translations, stage productions, as set work on school and university syllabi – becoming, in the process, arguably South Africa's most canonical, transnational, novel. This article reflects on my own personal, family and academic history of engagement with the novel over almost four decades, and the differing readings and responses which it has elicited. In so doing, the article tries to shed light not just on Paton's novel, but on questions of use, value and meaning in our encounters with literary texts which seem, insistently, to demand our renewed attention.